Trends in trawl and purse seine catch rates in the north-eastern Mediterranean - MACHIAS, A.; STERGIOU, K.I.; SOMARAKIS, S.; KARPOUZI, V.S.; KAPANTAGAKIS, A. (Mediterranean Marine Science, 2008)
Data on fishing effort expressed in vessel days at sea and corresponding landing/day for a large number of species have been collected by the Institute of Marine Biological Resources (IMBR) since the second half of 1995. Data were collected over a grid of 21 stations throughout the Greek seas. In the present study we analyzed the monthly days at sea as well as catch per day for trawlers and purse seiners from 1996 to 2000, by general linear models and trend analysis. The following vessel size groups per gear were considered: (a) trawlers smaller and larger than 20m; (b) purse-seiners smaller and larger than 15m. Collected data were also aggregated for five fishing sub-areas: the North Aegean, the Central Aegean, the South Aegean, Cretan waters and the Ionian Sea. Trend analysis of landing/day time series indicated that demersal and pelagic resources are declining in the main fishing grounds. Declining landing/day trends are regarded as indicators of overfishing, especially in the light of the fact that high catch rates are maintained by fishing in ‘hot spots’. The results of the present analysis provide, for the first time, important information on the sustainability of the fisheries in the north-eastern Mediterranean, an area characterized by a complete lack of accurate long-term data on effort and catch per effort